Assessment of perception and effectiveness of concept mapping in learning epidemiology - Urvish Joshi; Sheetal Vyas (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: Current programs in medical education technology concentrate mainly upon "how-to-teach." The focus is needed on learner's memory retention too. An innovative strategy like concept mapping might be a way forward. The study was carried out to assess its effectiveness and to know students' perceptions. Materials and Methods: During community medicine classes, a student-group was sensitized on how to make and use concept maps out of taught contents. At the end of epidemiology exercises sessions, this group was given additional minutes to prepare concept maps, interact, and brainstorm followed by quick QA session. Others were taught same contents in conventional way. Performances of both groups were assessed in one immediate (term-ending) and one distant (preliminary) exam. Feedback was also taken from study group. Results: Study group consistently scored higher in both exams. Difference in scored mean marks was highly significant in term-ending-examination (P < 0.0001, t = 5.754, df = 121.9). Largely positive feedback was received on utility of concept maps in memorizing, confidence-boosting, and understanding subject. Felt need for innovations in conventional teaching-learning (T-L) was palpable. Conclusion: Time has come to start focusing on enhancing students' learning. Performance-enhancing utility of concept maps is proven and should be integrated in regular T-L.